2021
DOI: 10.33448/rsd-v10i3.13408
|View full text |Cite
|
Sign up to set email alerts
|

From olive to olive oil: a general approach

Abstract: This study aimed to carry out a systematic literature review about olives, extraction methods, physical and chemical characterization and identity and quality parameters of olive oils, as well as technological alternatives for using by-products. Olive oil is the oil extracted from the ripe fruits of the olive tree (Olea europaea L.). Trees have been cultivated in the Mediterranean Region for several centuries and thousands of cultivars differ by weight, size and chemical characteristics of the fruits. Currentl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
0
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 62 publications
(83 reference statements)
0
0
0
3
Order By: Relevance
“…Algumas décadas atrás, o cultivo de oliveira estava limitado a países localizados na bacia do Mediterrâneo, como a Espanha, Itália e Grécia. Atualmente, no entanto, o cultivo de oliveira expandiu-se consideravelmente para áreas fora da região do Mediterrâneo, incluindo Nova Zelândia, Austrália, Argentina, Chile, Uruguai e Brasil (Crizel et al, 2020;Silva et al, 2021).…”
Section: Introductionunclassified
See 2 more Smart Citations
“…Algumas décadas atrás, o cultivo de oliveira estava limitado a países localizados na bacia do Mediterrâneo, como a Espanha, Itália e Grécia. Atualmente, no entanto, o cultivo de oliveira expandiu-se consideravelmente para áreas fora da região do Mediterrâneo, incluindo Nova Zelândia, Austrália, Argentina, Chile, Uruguai e Brasil (Crizel et al, 2020;Silva et al, 2021).…”
Section: Introductionunclassified
“…O Brasil é um dos maiores importadores de produtos de oliveira da América do Sul (Pio et al 2005;Crizel et al, 2020;Silva et al, 2021). Apesar do interesse crescente pela cultura, a olivicultura no Brasil ainda é consideravelmente baixa, devido principalmente a manejos inadequados e conhecimento deficiente de modernas técnicas de formação e condução dos pomares.…”
Section: Introductionunclassified
See 1 more Smart Citation
“…Several studies confirmed that olive oil consumption results in benefits whether for human health or disease prevention such as antioxidants (Bartolomei et al, 2021;Kouka et al, 2017), anticancer (Buckland et al, 2012;Owen et al, 2004;Psaltopoulou et al, 2011), antibacterial (Karygianni et al, 2019;Nazzaro et al, 2019), and antidiabetic (Jurado-Ruiz et al, 2019;Yubero-Serrano et al, 2019). The sensory profile of olive oil is also affected by the variety of olive, climatic, and extraction methods where the sensory profile has a direct impact on economic value (Silva & Schmiele, 2021).…”
Section: Olive Oil (Oo)mentioning
confidence: 94%